Students as partners to organize an international conference. What did they learn? - Kouri, Pirkko; Ahonen, Outi Maria (Finnish Journal of eHealth and eWelfare, 2018)
In Finland higher education system consists of both theoretical universities and universities of applied sciences (UASs). Today students in higher education institutions are encouraged to find their way and teaching and learning occurs in different environments. A scientific conference provides prerequisites for high-quality, working-life based higher education experience as well as familiarizes with research, development and innovation practices. Furthermore, an international conference offers both new possibilities to disseminate one’s research and development work and to build international co-operation and new networks. The Finnish Society for Telemedicine and eHealth (FTeHS) works on voluntary basis and needs extra help in conference building. This offers a great opportunity to cooperation with students. The recruitment criteria for the students were e.g. prior experience in conferences or equivalent, and good English language skills. The master level students, five of them, were chosen in late autumn 2017 from the two Universities of Applied sciences. The article enlightens students’ experiences related to the preparatory and execution phases of the conference. The instructions are given what the conference work is. The article describes how students are planning, realizing and evaluating the conference in collaboration with conference organizations, and simultaneously having a fruitful and many-sided learning experience. The research data was collected via meeting notes made by the student in meeting’s secretary role, students’ learning reports, emailing messages and WhatsApp messages. Article focuses on student’s learning more than teaching.